Training on the Use of EduStory-Gen for Developing Interactive Storytelling among Kindergarten and Early Childhood Education Teachers - Junadhi Junadhi; Sarjon Defit; Okfalisa Okfalisa (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: Early childhood education plays an important role in supporting children’s cognitive, social, and emotional development. However, many kindergartens and early childhood education teachers continue to rely on conventional storytelling approaches and have limited experience in utilizing digital and artificial intelligence (AI)-based technologies for learning activities. Contribution: This community service program contributes to teacher professional development by introducing EduStory-Gen, an AI-assisted storytelling platform that integrates narrative generation and visual illustration creation. Method: The program employed a participatory training approach involving 30 kindergarten and early childhood education teachers. The activities included needs analysis, training preparation, pre-assessment, hands-on training, mentoring, and post-training evaluation. Results: The results showed substantial improvements in teachers’ competencies related to digital storytelling and AI-assisted educational tools. The average competency score increased from 2.9 in the pre-assessment to 4.4 in the post-assessment. The highest improvement was observed in teachers’ knowledge of AI-based tools (+1.7). Conclusion: The EduStory-Gen training program effectively enhanced teachers’ digital storytelling competencies and AI literacy while fostering positive learning experiences. The findings highlight the potential of AI-assisted storytelling tools to support innovative teaching practices and strengthen technology integration in early childhood education.